2016
DOI: 10.18632/oncotarget.9880
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of long non-coding RNA expression profiles in hepatitis B virus-related hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common kinds of malignancies and is closely correlated with hepatitis B virus (HBV) infection. Recent evidence has proved that long non-coding RNAs (lncRNAs) are implicated in development and progression of cancer. However, the contributions of lncRNAs to HBV-related HCC remain largely unknown. Here, we comprehensively investigated lncRNA expression profiles in HBV-related HCC by annotating and analyzing microarray datasets. By analyzing 42 HCC tissue samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…We compared the differentially expressed mRNA and lncRNA with previous studies. For example, BAIAP2-AS1 [ 24 ], THBS4 [ 25 ] are also over-expressed in our samples, which supports the reliability of our study. Although the difference of BAIAP2-AS1expression did not reach statistical significance, which may be due to the small number of samples analyzed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We compared the differentially expressed mRNA and lncRNA with previous studies. For example, BAIAP2-AS1 [ 24 ], THBS4 [ 25 ] are also over-expressed in our samples, which supports the reliability of our study. Although the difference of BAIAP2-AS1expression did not reach statistical significance, which may be due to the small number of samples analyzed.…”
Section: Discussionsupporting
confidence: 88%
“…Pan et al and Yu et al analyzed the lncRNA expression profiles between HBV-related HCC tissues and corresponding normal liver tissues using microarrays without characterizing the function of a specific lncRNA, respectively [ 22 , 23 ]. Gong et al investigated lncRNA expression profiles in HBV-related HCC by annotating and analyzing microarray datasets and identified 182 lncRNAs that were specifically differentially expressed in HBV-related HCC [ 24 ]. A recent study reported the expression profile on lncRNA among 5 male HBV-induced HCC cases by using microarray analysis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of translated proteins, lncRNAs were considered "transcription noise" or "junk RNA". However, lncRNAs have already been shown to be a key factor in the regulation of gene expression, especially in cancer research (Gong et al, 2016;Huang et al, 2016;Jiang et al, 2016;Zhang et al, 2015). Recent studies demonstrated that viral infection can alter host lncRNA expression profile.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is known as the most common liver malignancy worldwide, with extremely high incidence and mortality rate ( 1 5 ). In China, HCC frequently occurs owing to chronic infection of hepatitis B virus (HBV) ( 6 9 ). Other conditions, such as alcoholic hepatitis, non-alcoholic fatty liver disease, hemochromatosis and diabetes, also contribute to the development of HCC ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%